Multi-level cyber security system for VANET - Muntadher Naeem Yasir; Muayad Sadik Croock (Institute of Advanced Engineering and Science, 2020)
Recently, the cyber security of vehicular ad-hoc network (VANET) including two practicable: car-to-car and car-to-infrastructure has been considered due to importance. It has become possible to keep pace with the development in the world, where the safety of people is a priority in the development of technology in general and in particular in the field of VANET. In this paper, a cyber security system for VANET has been proposed to tackle the DOS attacks. The proposed system includes three security levels. Firstly, the registeration level that ask vehicles to be registered in the system, in which the network exclude the unrigestered ones. Secondly, the authentication level that checks the vehicles before joining the network. This is done by applying a proposed algorithm that considers the hash function and factory number. Thirdly, the proposed system ables to detect the DOS attack by any involved vehicle using the monitoring algorithm that allocate such vehicle to be excluded from the network. The obtained results show the efficient performance of the proposed system in managing the security of the VANET network. The multi-level system increases the security of the network, in which the attacks can be eliminated.